A framework for defining both qualitative and quantitative supplier selection criteria considering the buyer-supplier integration strategies - Sen, S.; Basligil, H.; Sen, C. G.; Baracli, H. (TAYLOR & FRANCIS LTD, 2008)
Previous research has reported that the decision criteria used to evaluate suppliers differ by product category. This paper presents a framework for defining the supplier selection criteria by investigating possible quantitative and qualitative criteria reported by earlier studies according to the levels of buyer-supplier relationship, the company's competitive situation and its corporate strategies, rather than investigating these criteria in respect of product category. The solution proposed in this study not only assists decision makers to define selection criteria, but also supports determining the buyer-supplier integration level. An actual case in Audio Electronics, a Turkish electronics business, demonstrates the feasibility of applying the proposed framework in practice.
Keywords: supplier selection; buyer-supplier integration levels; formulation of criteria; decision making; ANALYTIC HIERARCHY PROCESS; VENDOR SELECTION; SYSTEM; Engineering; Operations Research & Management Science